Geographical Distribution of Pleural Effusion among Hospitalized Patients in Jember Pulmonary Hospital - Annisa Fitrah Aini; Adistha Eka Noveyani (Caring: Indonesian Journal of Nursing Science, 2023)
Pleural effusion (PE) is a pathological condition that frequently develops in individuals with thoracic or systemic disorders, and if not recognized and treated promptly, it can have fatal consequences. This study aims to describe the epidemiology (distribution of person, time, and location) of pleural effusion among hospitalized patients. Medical records of all patients diagnosed with pleural effusion from July 2022 to June 2023 were reviewed and analyzed. The study included all hospitalized patients found to have pleural effusions, totalling 315 patients. This research used a quantitative descriptive survey, with data analyzed using spatial analysis with GIS across five districts. Patients were analyzed for socio-demographic characteristics and epidemiological distribution, including the level of diagnosis, health assurance type, frequency between months, and geographical distribution, which was analyzed spatially. The highest number of pleural effusion cases among hospitalized patients were in men (57.5%), aged between 46 and 65 years (49.2%), employed as entrepreneurs (20%), non-premium Assistance Beneficiaries for medical bill payment status (47.3%), and mostly with pleural effusion as a secondary diagnosis. The number of pleural effusion cases fluctuated, with distribution in several subdistricts from the five districts in the Jember Pulmonary Hospital. The highest cases were reported in two districts, Jember Regency and Banyuwangi Regency. Population density could be a factor that increases the risk of pleural effusion. A multidisciplinary approach is needed for optimal management.